Aortic Valve Replacement in a Patient With Right Coronary Artery Anomaly - Cetin, Secil; Zorman, Yilmaz; Yaylak, Doruk; Kalangos, Afksendiyos (Journal of Humanitarian Cardiovascular Medicine, 2025)
Anomalous coronary arteries, though rare, may complicate cardiac surgery. We present a 75-year-old male scheduled for aortic valve replacement after incidental detection of severe aortic stenosis. Preoperative imaging revealed a right coronary artery originating from the left sinus of Valsalva, coursing between the aorta and pulmonary artery. Following implantation of a 23-mm prosthetic valve, the patient developed hypotension and right ventricular dysfunction during separation from cardiopulmonary bypass. Transesophageal echocardiography suggested prosthetic-induced coronary compression. The valve was downsized to 21 mm, and a prophylactic coronary artery bypass graft was placed. Hemodynamics stabilized, and the patient was successfully weaned from bypass and discharged uneventfully. This case highlights the critical role of preoperative imaging, intraoperative adaptability, and multidisciplinary collaboration in managing coronary anomalies during valve surgery.